Determinant of Adherence to iron supplementation in Adolescent Girl In Spesific Intervention For Stunting Prevention: Systematic Review - Alma Feriyanti; Nafiatus Sintya Deviatin; Ira Nurmala; Sri Widati; Dominikus Raditya Atmaka (Universitas Airlangga, 2022)
An increase in the prevalence of anemia in young women will affect the quality of life and their offspring. Adolescent girls who experience anemia are at risk for anemia during pregnancy. Anemia in pregnant women will impact giving birth to stunted babies. Iron supplementation is a specific intervention effort to prevent anemia in female adolescents. This study aims to analyze the determinants of adherence to iron supplementation in young women and specific interventions to prevent stunting. This study uses a systematic review using PRISMA. Five electronic databases are used: Scopus, ScienceDirect, Wos, SAGE, and Google Scholar. The articles used in this research are 10 articles. The inclusion criteria for this study were articles published within five years, namely, 2018-2022, full text, open access, and in Indonesian and English. The determinants of adherence to iron supplementation are influenced by several factors, including sociodemographic factors such as the mother's occupation, education, and adolescent age. Intrapersonal factors such as young women's motivation and perceived benefits. Interpersonal factors such as support from parents, peers, and teachers. Institutional factors such as school support in the distribution of iron tablets. The compliance of young women in consuming iron tablets is influenced by sociodemographic, intrapersonal, intrapersonal, and institutional factors. There is a need for health education for young women and parents as well as strengthening commitment to schools so that they receive support in the implementation of iron supplementation as a specific intervention for stunting prevention Keywords: Compliance, Iron Tablets, Adolescents, Anemia, Stunting